The Effectiveness of Choice Theory Education on Reducing Work-Family Conflict of Women - Varzaneh 1, Abolfazl Hatami; Rostami 2*, Farahnaz; Fathi 1, Elham (Shahroud Journal of Medical Sciences, 2020)
Background: One of the most significant issues of areas of work and family interactions is work-family conflict. Dominant traditional and stereotypical attitudes toward women’s roles and doing institutionalized house chores provoke problems such as a decline in organizational performance and adverse physical, mental, and behavioral effects in women. The purpose of this study was to explore the effectiveness of choice theory education on reducing work-family conflict of women working in the hospital. Methods: The quasi-experimental research conducted in a pre-test and post-test control group design aimed to examine the effectiveness of the choice theory education on reducing work-family conflict of 12 participants in the experimental group and 12 participants in the control group who were selected by multistage cluster sampling. Results: The result of Covariance analysis revealed that there was a significant difference between the experimental and control group in post-test (Pvalue< 0.001, F=50.13).Conclusions: It can be concluded that the education of choice theory's concepts can be used as one of the strategies of reducing the work-family conflict to confront its negative consequences in organizations and families.